2020
DOI: 10.3390/ijms21144959
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Pathophysiological Aspects of Primary Cilia—A Literature Review with View on Functional and Structural Relationships in Cartilage

Abstract: Cilia are cellular organelles that project from the cell. They occur in nearly all non-hematopoietic tissues and have different functions in different tissues. In mesenchymal tissues primary cilia play a crucial role in the adequate morphogenesis during embryological development. In mature articular cartilage, primary cilia fulfil chemo- and mechanosensitive functions to adapt the cellular mechanisms on extracellular changes and thus, maintain tissue homeostasis and morphometry. Ciliary abnormalities in osteoa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…We found no differences in cilium strains between the 0-and 180-degree orientations of cilia in the present study. The orientation of the cilium has been noted to be disrupted in cartilage diseases such as osteoarthritis, osteochondroma, and chondrosarcoma [10,31,32,33]. In the PZ and HZ of growth plate cartilage, primary cilia are present at the top or bottom of the cell and oriented towards the subchondral bone or towards the metaphysis.…”
Section: Discussionmentioning
confidence: 99%
“…We found no differences in cilium strains between the 0-and 180-degree orientations of cilia in the present study. The orientation of the cilium has been noted to be disrupted in cartilage diseases such as osteoarthritis, osteochondroma, and chondrosarcoma [10,31,32,33]. In the PZ and HZ of growth plate cartilage, primary cilia are present at the top or bottom of the cell and oriented towards the subchondral bone or towards the metaphysis.…”
Section: Discussionmentioning
confidence: 99%
“…The primary cilium is the center for the Hh signaling transduction; thus, the relationship between cilia and osteochondromas and enchondromas has been investigated. In osteochondroma, the primary cilium incidence was normal, but the cilium orientation was dramatically disrupted compared with control [ 28 ]. Cilium organization is essential for cells' polarity, and the disorganized cilium orientation in most cells of osteochondromas may contribute to the loss of cell polarity and arrangement in the growth plate [ 29 ].…”
Section: Primary Cilia and Ciliary Proteins In Skeletal Diseasesmentioning
confidence: 99%
“…Cilium organization is essential for cells' polarity, and the disorganized cilium orientation in most cells of osteochondromas may contribute to the loss of cell polarity and arrangement in the growth plate [ 29 ]. However, the cilium incidence in enchondroma is reported to vary in different studies [ 28 ]. Ho et al [ 30 ] reported that only 13.4% of cells are ciliated in enchondroma tissues, which significantly decreased compared with control articular cartilage ( Figure 1 ).…”
Section: Primary Cilia and Ciliary Proteins In Skeletal Diseasesmentioning
confidence: 99%
“…Cilia have also been implicated in conditions such as diabetes, cancer, congenital heart disease and osteoarthritis. [3][4][5] As cilia have a near-ubiquitous anatomical distribution, genetic defects affecting the structure or function of cilia cause a range of conditions that can affect multiple organs. Ciliopathies are typically classified into: retinal ciliopathies that exclusively or predominantly affect the eye 6 ; renal ciliopathies, which include autosomal dominant polycystic kidney disease affecting around 1:500 people 7 ; skeletal ciliopathies that cause a diverse range of skeletal dysplasias and cranio-facial dysmorphology 8 ; metabolic or 'obesity' ciliopathies 9 ; neurodevelopmental ciliopathies 10 ; and the respiratory motile ciliopathies.…”
Section: Introductionmentioning
confidence: 99%
“…They encompass a range of severe developmental and degenerative diseases that are individually rare but collectively common, affecting an estimated 15.8 million people worldwide including an estimated 133 000 people in the UK. Cilia have also been implicated in conditions such as diabetes, cancer, congenital heart disease and osteoarthritis 3–5. As cilia have a near-ubiquitous anatomical distribution, genetic defects affecting the structure or function of cilia cause a range of conditions that can affect multiple organs.…”
Section: Introductionmentioning
confidence: 99%